2011
DOI: 10.1302/0301-620x.93b6.25804
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of metal ion levels in the joint fluid of symptomatic patients with metal-on-metal hip replacements

Abstract: We retrospectively analysed concentrations of chromium and cobalt ions in samples of synovial fluid and whole blood taken from a group of 92 patients with failed current-generation metal-on-metal hip replacements. We applied acid oxidative digestion to our trace metal analysis protocol, which found significantly higher levels of metal ion concentrations in blood and synovial fluid than a non-digestive method. Patients were subcategorised by mode of failure as either 'unexplained pain' or 'defined causes'. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 24 publications
4
83
2
Order By: Relevance
“…The correlation is statistically significant both for Co and Cr but is slightly higher for the ion cobalt. In the absence of particles in the synovial fluid, the circulating values of Cr or Co are lower than 7 ppb in 15 cases out of 16 and establishing values slightly higher than that proposed by Estey et al [15], suggesting 4 ppb as normal threshold level of ions for asymptomatic subjects. With the increase of the number of Co-Cr particles isolated in the synovial fluid, the level of circulating ions increases.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The correlation is statistically significant both for Co and Cr but is slightly higher for the ion cobalt. In the absence of particles in the synovial fluid, the circulating values of Cr or Co are lower than 7 ppb in 15 cases out of 16 and establishing values slightly higher than that proposed by Estey et al [15], suggesting 4 ppb as normal threshold level of ions for asymptomatic subjects. With the increase of the number of Co-Cr particles isolated in the synovial fluid, the level of circulating ions increases.…”
Section: Discussionmentioning
confidence: 52%
“…Davda et al measured the levels of Co and Cr ions present in the synovial fluid of patients with prostheses without evaluating the presence of particles; they therefore showed that the analytical method foreseeing acid oxidative digestion causes a significant increase in metal ions measured in the fluid, therefore indirectly proving that nanoparticles are present in the fluid and contribute to the total local content of cobalt and chromium [16].…”
Section: Measurementioning
confidence: 99%
See 2 more Smart Citations
“…In well‐functioning prostheses at 10‐year follow‐up, median Co and Cr concentrations in the circulation have been reported to be 0.75 μg/L (range: 0.3–50.1 μg/L) and 0.95 μg/L (range: 0.3–58.6 μg/L) respectively 17. Periprosthetic concentrations are several fold higher (median Co, 113 μg/L; median Cr, 54 μg/L),18 while patients with failing prosthesis have reported Co and Cr concentrations as high as 528 μg/L (range: 0–13,000 μg/L) and 1,844 μg/L (range: 0–38,600 μg/L), respectively 19. We recently demonstrated that exposure to Co 2+ and Cr 3+ adversely affects both osteoclast and osteoblast survival and function, including the mineralization of prosthesis surfaces in vitro, at concentrations equivalent to those found clinically 20, 21, 22…”
mentioning
confidence: 97%